الصوامت المجهورة والمهموسة في اللغتين العربية والملايوية: دراسة تقابلية - Zulkipli Md. Isa; Wan Moharani Mohammad; Sulaiman Ismail; Muhammad Marwan Ismail; Arnida A. Bakar; Wahida Mansor; Farah Nadia Harun (Universiti Sains Islam Malaysia, 2026)
International Conference of Language & Education (iLEC2025): Empowering Language and Education to Develop Madani Generation in the Era of Artificial Intelligence (AI) 17 & 18 November 2025 Organized by Universiti Sains Islam Malaysia